PRODUKSI DAN APLIKASI ARANG KOMPOS BIOAKTIF DI LAHAN PERTANIAN SEBAGAI MODEL PEMBERDAYAAN MASYARAKAT - Nur Adi Sapura; Gusmailina; Sri Komarayati; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2022)
Community empowerment has been carried out at the Kumala Lestari Islamic boarding school, located in Sukaresmi Village,Cianjur Regency, Indonesia. The community was involved in the manufacture of bioactive compostable charcoal (ARKOBA) andits application in agricultural areas. The study was conducted through comparison of rice planting using chemical fertilizers-pesticidesand those with ARKOBA-liquid smoke. The yield amount was measured by paddy crop productivity per hectare after 4 monthperiod. The study was conducted by production of biochar from sawmill waste using a modified drum reactor. The reactor temperaturewas set into 400–450°C, while the retention time was set into 6 hours. The process produces charcoal and liquid smoke.ARKOBA production was carried out by mixing compost: charcoal: activator, with a composition of 85%: 10%: 5%. Meanwhile,the ARKOBA dose was set to 400 kg/1000m2. The result shows that the productivity of rice threated was higher than those ofchemical fertilizers. Rice productivity was recorded at 3.2 tons/ha against 2.98 tons/ha in the Ciranjang and 4 tons/ha comparedto 3.1 tons/ha in the Sukaresmi demonstration plot. Mixing ARKOBA and liquid smoke threatment provides a surplus ofaround 7.4–29% than chemical applications and becomes recommended technology for increasing rice productivity.